Review: Use of Electrophysiological Techniques to Study Visual Functions of Aquatic Organisms - Gao, Xiaolong; Lin, Shihui; Zhang, Mo; Lyu, Mingxin; Liu, Yafeng; Luo, Xuan; You, Weiwei; Ke, Caihuan (Frontiers in Physiology, 2022)
The light environments of natural waters have specific characteristics. For the majority of aquatic organisms, vision is crucial for predation, hiding from predators, communicating information, and reproduction. Electroretinography is a diagnostic method for assessing visual function. An electroretinogram (ERG) records the comprehensive potential response of retinal cells under light stimuli and divides it into several components. Different wave components are derived from different retinal cells, thus retinal function can be explored by analyzing these components. This review provides an overview of the milestones of ERG technology, describes how ERG is used to study visual sensitivity (e.g., spectral sensitivity, luminous sensitivity, temporal resolution) of fish, crustaceans, mollusks and other aquatic organisms (seal, sea lion, sea turtle, horseshoe crab, jellyfish), and reveals the correlation between visual sensitivity and habitat, the variation of visual sensitivity as a function of individual growth, and the diel changes of visual sensitivity. Efforts to identify the visual sensitivity of different aquatic organisms are vital to understanding the environmental plasticity of biological evolution and for directing aquaculture, marine fishery, and ecosystem management.